Positive electrode active material and lithium ion battery
Patent Information
- Application Number
- CN202611187485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]目前常规21700锂离子电池多采用普通中低镍正极材料、常规碳基负极及普通电解液体系,缺乏同时兼顾高镍高容量、低产气、高安全、长循环的21700圆柱形锂离子电池整体方案,尤其缺少高镍宽域配比、多粒度级配协同优化的正极材料体系设计,无法适配高端储能、大功率电动工具的高能量密度、高稳定性使用需求
正极活性材料采用特定元素含量的活性物质,以及活性物质自身为不同粒径混匀而成,实现了高容量、长循环、低产气与高安全的综合性能突破,以使产品具有优异的循环稳定性和低产气特性,卓越的高温存储性能和可靠地过充安全防护,以及优异的滥用安全性能。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a positive electrode active material and a lithium-ion battery. Background Technology
[0002] As terminal devices continue to demand higher requirements for battery capacity, cycle life, high-temperature stability, and safety performance, the shortcomings of traditional 21700 type (outer diameter 20.8mm-21.5mm, height 64.8mm-71.2mm) lithium-ion batteries are becoming increasingly apparent.
[0003] Currently, most conventional 21700 lithium-ion batteries use ordinary low- to medium-nickel cathode materials, conventional carbon-based anodes, and ordinary electrolyte systems. There is a lack of a comprehensive solution for 21700 cylindrical lithium-ion batteries that simultaneously achieves high nickel content, high capacity, low gas production, high safety, and long cycle life. In particular, there is a lack of cathode material system designs with high nickel wide-range ratios and multi-particle size gradation optimization, which cannot meet the high energy density and high stability requirements of high-end energy storage and high-power power tools.
[0004] Based on this, the present invention proposes a novel cylindrical lithium-ion battery structure and a highly adaptable cathode material system, which solves many defects of the prior art.
[0005] It should be noted that the information disclosed in the background section above is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute prior art known to those skilled in the art. Summary of the Invention
[0006] To provide a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended as a general commentary, nor is it intended to identify key / important components or describe the scope of these embodiments, but rather as a prelude to the detailed description that follows.
[0007] Currently, conventional 21700 lithium-ion batteries have the following technical challenges: First, the electrolyte decomposes severely during battery cycling and high-temperature storage, resulting in a large amount of gas production from the battery, which can easily lead to battery bulging and expansion, significantly reducing battery cycle life and storage stability. Second, conventional high-nickel cathodes have a low upper limit for nickel content, which limits the improvement of energy density. Moreover, they often use thick inorganic coatings, which have poor coating uniformity and are prone to agglomeration. At the same time, the particle size uniformity is poor, the gradation is unreasonable, the interparticle gaps and pore structures are disordered, the electrolyte wetting is uneven, long-term cyclic stress concentration is obvious, side reactions are aggravated, and thermal stability is insufficient. Third, the high-nickel cathode material system has poor compatibility. Under abuse conditions such as overcharging, short circuit, needle penetration, and extrusion, heat accumulates severely, the surface temperature is too high, and there is a risk of fire and explosion. Fourth, the battery has a high thickness expansion rate under cycling and high temperature conditions, poor battery structural stability, and is prone to problems such as electrode delamination and increased internal resistance after long-term use. Fifth, the pressure parameters of the explosion-proof cap and CID protection are not well matched, making it impossible to release pressure and cut off power in time under abnormal working conditions, resulting in low reliability of safety protection.
[0008] This invention addresses the limitation of existing technologies by providing a more comprehensive solution. It offers a positive electrode active material and a lithium-ion battery that overcomes the current lack of high-nickel, wide-range ratio, and multi-size gradation optimization in positive electrode material systems, thus failing to meet the high energy density and stability requirements of high-end energy storage and high-power power tools. The solution involves a complex combination of techniques, including improving the elemental composition of the positive electrode active material and effectively combining multiple particle sizes within the material itself. This application provides a positive electrode active material and a lithium-ion battery with measurable parameters and a clearly defined, synergistic formulation structure.
[0009] In some embodiments, a positive electrode active material includes an active substance with the following molecular chemical formula: LiNi x Co y Mn z M j O2, where M is a dopant element selected from at least one of Al, Zr, Mg, Ti, and La; satisfying: 0.80≤x≤0.96, 0.02≤y≤0.09, 0.02≤z≤0.09, 0.004≤j≤0.05, and x+y+z+j=1; The active material comprises particles of at least two sizes: a first particle and a second particle, wherein the median particle size D50 of the first particle is 8 μm-14 μm and the median particle size D50 of the second particle is 2 μm-5 μm; the mass percentage of the first particle is 50%-85% and the mass percentage of the second particle is 15%-50%.
[0010] In some embodiments, the tap density of the positive electrode active material is ≥1.50 g / cm³, and the specific surface area is 0.3 m² / g - 1.0 m² / g.
[0011] In some embodiments, a lithium-ion battery includes a positive electrode sheet coated with the positive electrode active material as described above, the coating surface density being 180 g / m². 2 -240g / m 2 The outer diameter of the lithium-ion battery is 20.8mm-21.5mm, and the height is 64.8mm-66.2mm.
[0012] In some embodiments, the positive electrode further includes an inorganic coating layer, which is disposed on the surface of the positive active material coating; the inorganic coating layer includes an inorganic compound layer containing at least one of aluminum, zirconium, magnesium, titanium, and lithium.
[0013] In some embodiments, the thickness of the inorganic coating layer is 3nm-12nm.
[0014] In some embodiments, the lithium-ion battery further includes an electrolyte containing a flame retardant additive, wherein the flame retardant additive has a percentage content of 1-5 wt%; the flame retardant additive is at least one of trimethyl phosphate, triethyl phosphate, and fluoroethylene carbonate.
[0015] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, which includes a negative current collector and a silicon-carbon composite material coated thereon, wherein a carbon coating layer with a thickness of 20nm-50nm is provided on the surface of the silicon-carbon composite material.
[0016] In some embodiments, the nominal capacity of the lithium-ion battery is 4-6 Ah; the gas production rate after 500 cycles at 25°C and 1C / 1C is ≤10 mL / Ah; the gas production rate after 30 days of storage at 60°C is ≤6 mL / Ah; and the maximum surface temperature after overcharging at 3C / 10V is ≤130°C.
[0017] In some embodiments, the lithium-ion battery further includes a cap assembly, wherein the explosion-proof opening pressure of the cap assembly is 1.7MPa-2.1MPa, and the CID opening pressure is 0.8MPa-1.1MPa.
[0018] In some embodiments, the lithium-ion battery satisfies at least one of the following conditions: (1) The highest surface temperature during the short-circuit test is ≤120℃; (2) The highest surface temperature during the needle penetration test is ≤150℃; (3) The thickness expansion rate during the cyclic process is ≤8%; (4) The thickness expansion rate after storage at 85℃ for 4 hours is ≤3%.
[0019] The positive electrode active material and lithium-ion battery provided in the embodiments of the invention can achieve the following technical effects: The positive electrode active material uses active substances with specific element content and is made by mixing active substances of different particle sizes. This achieves a comprehensive performance breakthrough with high capacity, long cycle life, low gas production and high safety, so that the product has excellent cycle stability and low gas production characteristics, excellent high temperature storage performance and reliable overcharge safety protection, as well as excellent abuse safety performance.
[0020] The above general description and the description below are exemplary and explanatory only, and are not intended to limit the invention. Detailed Implementation
[0021] To provide a more detailed understanding of the features and technical content of the embodiments of the present invention, the implementation of the present invention will be described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the present invention. In the following technical description, for ease of explanation, several details are used to provide a full understanding of the disclosed embodiments. However, one or more embodiments may still be implemented without these details.
[0022] In this embodiment of the invention, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion.
[0023] Unless otherwise stated, the terms “multiple” or “multi-multiple” mean two or more.
[0024] It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0025] This invention provides a positive electrode active material, comprising an active substance with the following molecular chemical formula: LiNi x Co y Mn z M j O2, where M is a dopant element selected from at least one of Al, Zr, Mg, Ti, and La; satisfying: 0.80≤x≤0.96, 0.02≤y≤0.09, 0.02≤z≤0.09, 0.004≤j≤0.05, and x+y+z+j=1; The active material comprises particles of at least two sizes: a first particle and a second particle, wherein the median particle size D50 of the first particle is 8 μm-14 μm and the median particle size D50 of the second particle is 2 μm-5 μm; the mass percentage of the first particle is 50%-85% and the mass percentage of the second particle is 15%-50%.
[0026] In this embodiment of the invention, the positive electrode active material uses the molecular chemical formula LiNi. x Co y Mn z M jThe active material of O2 has a range-limited composition of each element in the chemical formula, such as M being a dopant element selected from at least one of Al, Zr, Mg, Ti, and La; and 0.80≤x≤0.96, 0.02≤y≤0.09, 0.02≤z≤0.09, 0.004≤j≤0.05, and x+y+z+j=1; in particular, the active material of this chemical formula is designed in terms of physical structure, and the particles of at least two particle sizes are mixed to effectively reduce the rate of electrode side reactions, which is effectively verified in the specific embodiments below.
[0027] The two particle sizes of the active material are effectively set: the median particle size D50 of the first particle is 8μm-14μm, while that of the second particle is 2μm-5μm. Relatively speaking, the particle size of the first particle is larger than that of the second particle. In particular, the mass proportion of the first particle is 50%-85%, while that of the second particle is 15%-50%. The larger proportion of large particles allows small particles to fill the gaps between large particles, thereby reducing the porosity of the electrode sheet coated with the positive electrode active material, correspondingly reducing the amount of electrolyte wetting, inhibiting particle displacement and microcrack proliferation during cycling, and thus reducing gas production and thickness expansion rate.
[0028] In some embodiments, the tap density of the positive electrode active material is ≥1.50 g / cm³, and the specific surface area is 0.3 m² / g - 1.0 m² / g.
[0029] The embodiments of the present invention further define the structural characteristics of the positive electrode active material, including the tap density and specific surface area of the positive electrode active material; the tap density refers to the ultimate packing density reached after applying external forces such as vibration to the dry powder particle group of the positive electrode active material; while the specific surface area refers to the total area of a unit mass of positive electrode active material.
[0030] In some embodiments, a lithium-ion battery includes a positive electrode sheet coated with the positive electrode active material as described above, the coating surface density being 180 g / m². 2 -240g / m 2 The outer diameter of the lithium-ion battery is 20.8mm-21.5mm, and the height is 64.8mm-66.2mm.
[0031] This invention defines the structural parameters of a 21650 type lithium-ion battery, and combines this with a positive electrode sheet coated with the aforementioned positive active material, wherein the positive active material is coated on at least one side of the positive electrode sheet; the surface density of the positive active material coated on the side of the positive electrode sheet is set to 180 g / m². 2 -240g / m 2 .
[0032] The limitation on the coating surface density is a relative limitation on the coating method of the positive electrode active material on the positive electrode sheet, which is applicable to 21650 lithium-ion batteries and improves structural stability and high capacity.
[0033] In some embodiments, the positive electrode sheet further includes an inorganic coating layer, which is disposed on the surface of the positive electrode active material coating; the inorganic coating layer includes an inorganic compound layer containing at least one of aluminum, zirconium, magnesium, titanium and lithium.
[0034] In this embodiment of the invention, a coating is applied to the positive electrode active material on the positive electrode sheet. This coating layer is an inorganic coating layer, which is an inorganic compound layer containing at least one of aluminum, zirconium, magnesium, titanium, and lithium. Doping elements in the inorganic coating layer outside the positive electrode active material can stabilize the entire crystal structure. This coating layer can physically isolate Ni. 4+ It chemically absorbs HF with the electrolyte, synergistically suppressing side reactions.
[0035] More preferably, the thickness of the inorganic coating layer is 3nm-12nm.
[0036] This invention effectively reduces the rate of electrode side reactions by using a bimodal particle size distribution design of the positive electrode active material and a 3-12nm ultrathin inorganic coating layer.
[0037] In some embodiments, the lithium-ion battery further includes an electrolyte containing a flame retardant additive, wherein the flame retardant additive has a percentage content of 1wt%-5wt%; the flame retardant additive is at least one selected from trimethyl phosphate, triethyl phosphate, and fluoroethylene carbonate.
[0038] This invention provides an electrolyte configuration for a 21650 lithium-ion battery. The electrolyte is located inside the 21650 lithium-ion battery casing and is used to immerse the core. It also contains flame-retardant additives to prevent overheating and combustion. The flame-retardant additives are mainly at least one of trimethyl phosphate, triethyl phosphate, and fluoroethylene carbonate, accounting for 1wt%-5wt% of the total electrolyte, in order to improve battery safety.
[0039] In some embodiments, the lithium-ion battery further includes a negative electrode sheet, which includes a negative current collector and a silicon-carbon composite material coated thereon, wherein a carbon coating layer with a thickness of 20nm-50nm is provided on the surface of the silicon-carbon composite material.
[0040] This invention provides an improvement to the negative electrode sheet of a 21650 lithium-ion battery. The negative electrode current collector of the negative electrode sheet is coated with a silicon-carbon composite material, and a carbon coating layer with a thickness of 20nm-50nm is provided outside the silicon-carbon composite material to improve its conductivity.
[0041] In some embodiments, the nominal capacity of the lithium-ion battery is 4-6 Ah; the gas production rate after 500 cycles at 25°C and 1C / 1C is ≤10 mL / Ah; the gas production rate after 30 days of storage at 60°C is ≤6 mL / Ah; and the maximum surface temperature after overcharging at 3C / 10V is ≤130°C.
[0042] In some embodiments, the lithium-ion battery further includes a cap assembly, wherein the explosion-proof opening pressure of the cap assembly is 1.7MPa-2.1MPa, and the CID opening pressure is 0.8MPa-1.1MPa.
[0043] In some embodiments, the lithium-ion battery satisfies at least one of the following conditions: (1) The highest surface temperature during the short-circuit test is ≤120℃; (2) The highest surface temperature during the needle penetration test is ≤150℃; (3) The thickness expansion rate during the cyclic process is ≤8%; (4) The thickness expansion rate after storage at 85℃ for 4 hours is ≤3%.
[0044] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.
[0045] Example 1 This implementation case demonstrates a method for preparing a cylindrical lithium-ion battery by following these steps.
[0046] Method for preparing a positive electrode sheet: The positive electrode sheet includes a positive current collector aluminum foil and a positive electrode slurry coated on both sides of the current collector, wherein, calculated by mass percentage, the positive electrode slurry includes 96 wt% of the positive electrode active material LiNiO. 83 Co0. 06 Mn0. 06 Al0. 05 O2 (containing 70wt% polycrystalline and 30wt% monocrystalline, where the polycrystalline is the first particle and the monocrystalline is the second particle), 2wt% polyvinylidene fluoride (PVDF) binder and 2.0wt% conductive agent SP; the above substances are added to the solvent NMP and stirred to obtain a positive electrode slurry with a solid content of 68%, which is then coated on both sides of aluminum foil and dried to obtain a positive electrode sheet.
[0047] Method for preparing negative electrode sheet: The negative electrode sheet includes a copper foil as a negative electrode current collector and a layer of negative electrode active material coated on both sides of the current collector. The negative electrode coating comprises 96 wt% silicon carbon, 1.0 wt% conductive agent, 1.0 wt% thickener and 2 wt% binder by mass percentage. The above materials are added to deionized water as a solvent and stirred to obtain a negative electrode slurry with a solid content of 40%. The slurry is coated on both sides of the copper foil and dried to obtain the negative electrode sheet.
[0048] Electrolyte preparation method: Lithium salt (LiPF6 1.0M) is dissolved in an organic solvent, which is prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 3:5:2, wherein the additive is 2.0 wt% vinylene carbonate (VC), and finally the electrolyte is prepared.
[0049] Preparation method of the diaphragm: The diaphragm includes a high porosity diaphragm, a PE base membrane with a thickness of 9 μm, ceramic coatings on both sides with a thickness of 1 μm, and a PVDF coating with a thickness of 1 μm. The air permeability of the diaphragm is 100 s / 100 mL.
[0050] Assembly method: After the positive and negative electrode sheets are slit and die-cut using a winding machine, they are wound together with the separator to form a core. The core is then cut and stacked with positive and negative electrode tabs. The positive and negative busbars are then welded to the core, and the negative busbar is welded to the steel shell. An insulating sheet is placed on top of the positive busbar, and the positive busbar is then welded to the cap. Next, grooving, electrolyte injection, and sealing are completed. Finally, a formation process yields the experimental cylindrical battery. The cylindrical battery has an outer diameter of 21 mm and a height of 65 mm.
[0051] The design parameter settings for Examples 1-8 and Comparative Examples 1-7 are shown in Table 1 below: Table 1
[0052] The relevant performance of Examples 1-8 and Comparative Examples 1-7 is shown in Table 2 below: Table 2
[0053] As shown in Tables 1 and 2 above, the system comparison between Examples 1-8 and Comparative Examples 1-7 demonstrates that the synergistic configuration of the various technical features of the present invention is the key to achieving the excellent overall performance of the 21650 battery.
[0054] Comparative Example 1 used a single-peak particle size distribution, lacking small particles to fill the gaps between large particles, resulting in a high electrode porosity (approximately 35%). This increased the contact area between the electrolyte and the positive electrode active material, leading to microcrack proliferation during cycling and exposing fresh interfaces, exacerbating interfacial side reactions. Consequently, the gas production reached 12.5 mL / Ah (>10 mL / Ah) after 500 cycles, with a thickness expansion rate of 8.5%, failing to meet the requirements for cycle stability. In contrast, Example 1 used a bi-peak particle size distribution (large D50 = 11 μm / 70% + small D50 = 3.5 μm / 30%), with small particles filling the gaps between large particles, reducing electrolyte wetting, increasing inter-particle contact points, improving electron conduction, and suppressing particle displacement, reducing the gas production to 6.2 mL / Ah.
[0055] Comparative Example 4 removed the positive electrode coating layer, and the Ni on the surface of the high-nickel positive electrode... 4+ Direct exposure to the electrolyte catalyzes the oxidation and decomposition of the solvent, releasing CO2 and simultaneously producing H2O and HF. HF further corrodes the positive electrode and dissolves transition metal ions, which deposit on the negative electrode and damage the SEI film. The circulating gas production rate increases to 13.8 mL / Ah, and the gas production rate reaches 8.5 mL / Ah when stored at 60°C. The thickness expansion rate is as high as 4.2% at 85°C for 4 hours. However, in Examples 1 (8nm Al2O3) and 4 (12nm Al2O3), the physical isolation and chemical stabilization of the coating layer effectively suppressed the above side reactions, and the gas production rates were controlled at 6.2 and 5.8 mL / Ah, respectively. However, a thicker coating is not always better. In Comparative Example 5, when the coating was increased to 25 nm, the lithium-ion diffusion path was significantly prolonged, polarization was intensified, the specific capacity dropped to 185 mAh / g, the capacity dropped to 4.7 Ah, the overcharge temperature reached 106 °C, and the cycle gas production exceeded the limit (10.5 mL / Ah). This indicates that a thickness range of 3-12 nm is the optimal window for balancing interface protection and ion conduction.
[0056] The matching of the cap pressure system is equally crucial. Comparative Example 2 (explosion-proof plate 2.5MPa) suffered from excessively high opening pressure, causing the pressure accumulation rate to exceed the casing's capacity. Irreversible thermal runaway occurred inside the battery before the explosion-proof plate activated, resulting in overcharge temperatures of 121°C, short circuits of 135°C, and needle-puncture fire at 158°C. Comparative Example 6 (CID 1.3MPa) had an excessively high CID activation threshold. When the pressure reached 1.3MPa, the internal temperature of the battery exceeded 115°C, irreversibly triggering electrolyte vaporization and positive electrode oxygen release reactions, leading to an overcharge temperature as high as 135°C. The common failure mechanism for both was that the pressure setting exceeded the safe response window. Conversely, Comparative Examples 3 (explosion-proof plate 1.5MPa) and 7 (CID 0.5MPa) had excessively low pressure thresholds, causing accidental opening under normal cycling or slight transient pressure fluctuations. This resulted in battery seal failure and premature disconnection, respectively, rendering the battery unusable. Only Example 1 (explosion-proof sheet 1.9MPa / CID 0.95MPa), Example 7 (CID 1.05MPa), and Example 8 (explosion-proof sheet 1.75MPa) achieved a two-level safety response sequence of "first CID circuit cut-off, then explosion-proof sheet pressure relief protection" within the range of 0.8-1.1MPa / 1.7-2.1MPa, ensuring that the overcharge temperature is ≤95℃, and that there is no fire or explosion due to short circuit or needle puncture, and that all safety performances fully meet the standards.
[0057] In summary, the three technical features of bimodal gradation, coating layer control, and cap pressure matching constitute an inseparable organic whole. Deviation of any single variable will lead to excessive gas production, increased thermal runaway temperature, or premature structural failure, thus failing to simultaneously meet the four parallel thresholds of claim 1: cyclic gas production ≤10mL / Ah, storage gas production ≤6mL / Ah, overcharge temperature ≤130℃, and cap pressure range. This fully verifies the scientific nature and necessity of the technical solution of this invention.
[0058] The following is a brief introduction to the methods for testing seven performance parameters of the 21650 cylindrical lithium-ion battery of this invention: Test 1: High-temperature storage test at 60℃ and 100% SOC Take a cylindrical lithium battery prepared according to any of the above embodiments and test it according to the following steps: (1) Discharge the battery at a constant current of 0.1C until it reaches 2.5V cutoff, and let it stand for 5 minutes; (2) Charge the battery at a constant current of 0.2C until it reaches 4.2V and then charge it at a constant voltage until it reaches 0.05C. (3) Test the battery capacity at this time as the initial capacity; (4) Store the battery in a 60°C constant temperature chamber for 30 days.
[0059] The gas production test after storage at 60℃ for 30 days needs to be conducted by combining test method one and test method four.
[0060] Test 2: Capacity retention test at 25℃, 1C / 1C for 500 cycles Take a fresh battery, place it in a 25°C constant temperature chamber for more than 4 hours, and test it according to the following steps: (1) Discharge the battery at a constant current of 0.1C until it reaches 2.5V cutoff, and let it stand for 5 minutes; (2) Charge the battery at a constant current of 0.2C until it reaches 4.2V, then charge it at a constant voltage until it reaches 0.05C, and let it stand for 5 minutes. (3) Discharge the battery at a constant current of 0.2C until it is cut off at 2.5V, and let it stand for 5 minutes. Then read the capacity value C0 at this time. (4) Charge the battery at a constant current of 1.0C to 4.2V, and then charge it at a constant voltage of 0.05C until it stops, and let it stand for 5 minutes; (5) Discharge the battery at a constant current of 1.0C until it reaches 2.5V cutoff, and let it stand for 5 minutes; (6) Repeat steps (4) and (5) 500 times.
[0061] The gas production after 500 cycles of 1C / 1C needs to be determined by combining test method two and test method four.
[0062] Test 3: Overcharge Test Take a cylindrical lithium battery prepared according to any of the above embodiments, place it in a constant temperature chamber at 25°C for more than 4 hours, and test it according to the following steps: (1) Discharge the battery at a constant current of 0.1C until it reaches 2.5V cutoff, and let it stand for 5 minutes; (2) Charge the battery at a constant current of 0.2C until it reaches 4.2V, then charge it at a constant voltage until it reaches 0.05C, and let it stand for 5 minutes. (3) Discharge the battery at a constant current of 0.2C until it is cut off at 2.5V, and let it stand for 5 minutes; (4) Temperature sensing wires are attached to the head, middle and bottom of the battery cell to collect temperature signals. (5) Charge to 10V using 3C constant current, then switch to constant voltage charging for 1 hour, with a sampling interval of 1 second. (6) Let stand for 30 minutes (7) If the battery cell does not catch fire or explode, it is considered to pass, and the surface temperature of the battery is recorded.
[0063] Test 4: Gas Production Test Take a battery to be tested (pre-treated for cycling / storage / overcharge as required), place the battery and puncture needle into a sealed bag, fix the puncture needle at the weakest point of the battery, and heat-seal the bag after removing as much air as possible (vacuuming can be used as an aid). Completely immerse the sealed bag in the silicone oil in the water bath, securing it with clamps to prevent it from floating. Let it stand for 2-5 minutes until the liquid level stabilizes, then level the liquid level with the overflow port, placing a graduated cylinder below the overflow port (overflow method). Quickly puncture the battery casing with the puncture needle (recommended: center of the cap / explosion valve area) to release the internal gas. The sealed bag will expand due to the gas release, displacing the liquid. Wait for the liquid level to stabilize (approximately 3-5 minutes). Record the volume V of the overflowed liquid, and the gas production per unit capacity as V / C (C is the battery's nominal capacity in Ah).
[0064] Test 5: Short Circuit Test (1) Place the battery in a constant temperature chamber at 25±2℃ and let it stand for 30 minutes.
[0065] (2) Apply an external short circuit connection between the positive and negative terminals of the battery using a short circuit tester. The total circuit resistance is ≤5mΩ.
[0066] (3) Maintain the short circuit state until either of the following cutoff conditions is met: the short circuit duration is ≥360 minutes (6 hours); or the battery surface temperature drops by more than 80% of the maximum temperature rise; (4) Full-process data collection: short-circuit current, battery terminal voltage, and shell surface temperature.
[0067] (5) After the short circuit is cleared, observe for 1 hour and record whether there is fire, explosion, smoke, leakage, shell deformation, explosion-proof valve opening, CID action, etc.
[0068] Test 6: Needle Prick Test Take a battery and leave it in an environment of 25±2℃ for 24 hours. Charge it to full charge (100% SOC) with 1C constant current and constant voltage. Attach a thermocouple to the surface of the battery casing.
[0069] (1) Fix the battery vertically to the center of the test chamber using explosion-proof clamps.
[0070] (2) Set the diameter of the steel needle to Φ5-8mm.
[0071] (3) Penetrate the battery from a direction perpendicular to the battery plates at a speed of (25±5) mm / s.
[0072] (4) The penetration point is close to the geometric center of the pierced surface.
[0073] (5) The steel needle remains in the battery.
[0074] (6) Collect and record the following data throughout the process: voltage (sampling rate ≥ 100 Hz), temperature (accuracy ± 1 ℃), and pressure (range 0-50 kN).
[0075] (7) Observe for 1 hour and record whether there is fire, explosion, smoke, or leakage.
[0076] Test 7: Calculation of Thickness Expansion Rate Thickness expansion rate = (Battery thickness after cycling / after storage - Initial thickness) ÷ Initial thickness × 100% Therefore, the present invention has the following main technical contents: 1. Bimodal particle size distribution design of positive electrode active material Large particles have a D50 of 8-14 μm, while small particles have a D50 of 2-5 μm. Large particles account for 50%-85% of the total mass, and small particles account for 15%-50%. Small particles fill the gaps between large particles, reducing the porosity of the electrode, decreasing the amount of electrolyte wetting, and inhibiting particle displacement and microcrack growth during cycling, thereby reducing gas production and thickness expansion rate.
[0077] 2. Synergistic modification of high-nickel cathode materials through doping and coating The positive electrode active material has the chemical formula LiNixCoyMnzMjO2 (0.80≤x≤0.96, where M is at least one of Al, Zr, Mg, Ti, and La), and its surface is coated with an ultrathin inorganic layer of 3-12 nm (containing an inorganic compound of at least one of Al, Zr, Mg, Ti, and Li). The doping elements stabilize the crystal structure, and the coating layer physically isolates Ni. 4+It chemically absorbs HF with the electrolyte, synergistically suppressing side reactions.
[0078] 3. Precise matching of the two-stage safety pressure system for the cap. The explosion-proof diaphragm has an opening pressure of 1.7-2.1 MPa, and the CID (Clean Air Delivery System) has an opening pressure of 0.8-1.1 MPa. These two components form an ordered two-stage response: when the pressure rises to 0.8-1.1 MPa, the CID circuit is preferentially cut off; if the pressure continues to rise to 1.7-2.1 MPa, the explosion-proof diaphragm opens to release pressure, ensuring that the battery does not experience thermal runaway under abuse conditions such as overcharging.
[0079] The 21650 cylindrical lithium-ion battery provided by this invention achieves a breakthrough in comprehensive performance, including high capacity, long cycle life, low gas production, and high safety, through the synergistic design of the positive electrode material system, electrode structure, and safety devices. Specific beneficial effects include: (1) Excellent cycle stability and low gas production characteristics.
[0080] This invention utilizes a bimodal particle size distribution design for the positive electrode active material (large particles with a D50 of 8-14 μm accounting for 50%-85%, and small particles with a D50 of 2-5 μm accounting for 15%-50%), combined with a 3-12 nm ultrathin inorganic coating layer, to effectively reduce the rate of electrode side reactions. Examples 1-8, after 500 cycles at 25℃ and 1C / 1C, all exhibited gas production rates ≤7.5 mL / Ah, significantly lower than Comparative Example 1 (single-peak distribution, 12.5 mL / Ah) and Comparative Example 4 (no coating layer, 13.8 mL / Ah), with thickness expansion rates ≤7.2%, fully verifying the significant effect of the bimodal distribution and coating layer in synergistically suppressing gas production.
[0081] (2) Excellent high-temperature storage performance.
[0082] The coating layer on the cathode surface effectively isolates Ni from the surface of the high-nickel cathode (Ni content ≥ 80%). 4+ Direct contact with the electrolyte suppressed catalytic oxidation side reactions at high temperatures. After storage at 60°C for 30 days, the gas production of Examples 1-8 was ≤4.5 mL / Ah, significantly lower than Comparative Example 1 (7.2 mL / Ah) and Comparative Example 4 (8.5 mL / Ah). After storage at 85°C for 4 hours, the thickness expansion rate was ≤2.8%, while Comparative Example 4 reached 4.2%, demonstrating the effective suppression of high-temperature side reactions by the coating layer.
[0083] (3) Reliable overcharge safety protection.
[0084] By precisely matching the opening pressure of the explosion-proof disc (1.7-2.1MPa) with the opening pressure of the CID (0.8-1.1MPa), a two-stage safety response of "first CID cuts off the circuit, then the explosion-proof disc releases pressure for protection" is achieved. In Examples 1-8, the highest surface temperature during 3C / 10V overcharge was ≤95℃ (far below the 130℃ threshold), and the highest surface temperature during short-circuit testing was ≤108℃. In contrast, the overcharge temperature of Comparative Example 2 (explosion-proof disc 2.5MPa) reached 121℃, and the overcharge temperature of Comparative Example 6 (CID 1.3MPa) reached 135℃, both of which resulted in thermal runaway, proving the scientific validity of the cap pressure window setting.
[0085] (4) Excellent abuse safety performance.
[0086] The battery of this invention has a maximum surface temperature of ≤138℃ in the needle penetration test and does not catch fire or explode. In the extrusion test, it does not catch fire or explode when the deformation reaches 30%, thus fully meeting the safety requirements of power batteries.
[0087] The foregoing description fully illustrates embodiments of the invention to enable those skilled in the art to practice them. Other embodiments may include structural and other changes. The embodiments represent only possible variations. Individual components and functions are optional unless explicitly required, and the order of operation may vary. Some portions and features of some embodiments may be included in or replace portions and features of other embodiments. Embodiments of the invention are not limited to those already described above, and various modifications and changes can be made without departing from their scope. The scope of the invention is limited only by the appended claims.
Claims
1. A positive electrode active material, characterized in that, Including active substances with the following molecular chemical formula: LiNi x Co y Mn z M j O2, where M is a dopant element selected from at least one of Al, Zr, Mg, Ti, and La; satisfying: 0.80≤x≤0.96, 0.02≤y≤0.09, 0.02≤z≤0.09, 0.004≤j≤0.05, and x+y+z+j=1; The active material comprises particles of at least two sizes: a first particle and a second particle, wherein the median particle size D50 of the first particle is 8 μm-14 μm and the median particle size D50 of the second particle is 2 μm-5 μm; the mass percentage of the first particle is 50%-85% and the mass percentage of the second particle is 15%-50%.
2. The positive electrode active material according to claim 1, characterized in that, The tap density of the positive electrode active material is ≥1.50 g / cm³, and the specific surface area is 0.3 m² / g - 1.0 m² / g.
3. A lithium-ion battery, comprising a positive electrode, characterized in that, The positive electrode sheet comprises the positive active material as described in claim 1 or 2, with a coating surface density of 180 g / m². 2 -240g / m 2 The outer diameter of the lithium-ion battery is 20.8mm-21.5mm, and the height is 64.8mm-66.2mm.
4. The lithium-ion battery according to claim 3, characterized in that, The positive electrode sheet further includes an inorganic coating layer, which is disposed on the surface of the positive electrode active material coating; the inorganic coating layer includes an inorganic compound layer containing at least one of aluminum, zirconium, magnesium, titanium and lithium.
5. The lithium-ion battery according to claim 4, characterized in that, The thickness of the inorganic coating layer is 3nm-12nm.
6. The lithium-ion battery according to claim 5, characterized in that, The lithium-ion battery further includes an electrolyte containing a flame retardant additive, wherein the flame retardant additive has a content of 1-5 wt%; the flame retardant additive is at least one of trimethyl phosphate, triethyl phosphate, and fluoroethylene carbonate.
7. The lithium-ion battery according to claim 6, characterized in that, The lithium-ion battery also includes a negative electrode sheet, which includes a negative current collector and a silicon-carbon composite material coated thereon, wherein a carbon coating layer with a thickness of 20nm-50nm is provided on the surface of the silicon-carbon composite material.
8. The lithium-ion battery according to claim 7, characterized in that, The nominal capacity of the lithium-ion battery is 4-6 Ah; the gas production after 500 cycles at 25℃ and 1C / 1C is ≤10mL / Ah; the gas production after 30 days of storage at 60℃ is ≤6mL / Ah; and the maximum surface temperature after overcharging at 3C / 10V is ≤130℃.
9. The lithium-ion battery according to claim 8, characterized in that, The 21650 lithium-ion battery also includes a cap assembly, wherein the explosion-proof plate of the cap assembly has an opening pressure of 1.7MPa-2.1MPa, and the CID opening pressure is 0.8MPa-1.1MPa.
10. The lithium-ion battery according to claim 9, characterized in that, The 21650 lithium-ion battery meets at least one of the following conditions: (1) The highest surface temperature during the short-circuit test is ≤120℃; (2) The highest surface temperature during the needle penetration test is ≤150℃; (3) The thickness expansion rate during the cyclic process is ≤8%; (4) The thickness expansion rate after storage at 85℃ for 4 hours is ≤3%.